Assessing the State of ICZM in an Island Tourist Destination-Applying SESs and Ostrom's Collective Action Principles: A View from Coastal Communities - Arefipour, Tahereh; Alipour, Habib; Safaeimanesh, Farzad (Mdpi, 2022)
This paper aims to investigate the state of integrated coastal zone management (ICZM), which is justified as a strategy for managing coastal resources with respect to increasing pressures from tourism, farming, climate change, urbanization, population growth, etc. In the case of island states, the impact of tourism and second-home development is paramount. The use of coastal areas as commons and ICZM as a governance strategy have been established for a long time; however, the implementation of ICZM has remained a challenge due to the forces of global mass tourism and unsustainable resource use in island states. This study focused on views of the coastal communities in North Cyprus, who are in constant interaction with coastal ecosystems for their livelihood. For the analytical purpose of the study, 251 survey questionnaires were administered to eight communities along the coastal areas. Data analysis was conducted using descriptive statistical analysis with a post hoc test. Socio-ecological systems (SES) and Ostrom's collective action principles guided the study as the main theoretical frameworks. The study revealed that the ICZM strategy has been neglected and coastal communities are not invited to be involved in any form of ICZM. Furthermore, the study revealed the tourism development has been the major activity of the Anthropocene in coastal areas without a proactive coastal development strategy that is supposed to consider the vulnerability of coastal ecosystems. Practical and theoretical implications are also discussed.
Keywords: ICZM; coastal ecosystems; tourism; community; small island states; North Cyprus